2016
DOI: 10.1038/jid.2015.365
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Frizzled-Related Protein 2 (sFRP2) Functions as a Melanogenic Stimulator; the Role of sFRP2 in UV-Induced Hyperpigmentary Disorders

Abstract: In this study, we found that secreted frizzled-related protein 2 (sFRP2) is overexpressed in the hyperpigmentary skins of melasma and solar lentigo and in the acutely UV-irradiated skin. To investigate the effect of sFRP2 on melanogenesis, normal human melanocytes were infected with sFRP2-lentivirus or sh-sFRP2. It was found that sFRP2 stimulates melanogenesis through MITF/tyrosinase upregulation via β-catenin signaling. The stimulatory action of sFRP2 in pigmentation was further confirmed in melanocytes co-cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 39 publications
7
49
0
Order By: Relevance
“…A transcriptional analysis performed in melasma lesions compared to surrounding healthy skin then clearly emphasized the complexity of this disorder by revealing almost 300 genes to be significantly differentially regulated, affecting not only melanocytes but also the dermis component . These results further demonstrate that fibroblast-secreted factors, such as WIF1 (Kim, Lee, & Lee, 2013) or sFRP2 (Kim, Han, Kim, Park, & Kang, 2016), are involved in the pathophysiology of melasma. These data are in line with the reports that fibroblasts isolated from photoaging skin produce a greater amount of promelanogenic growth factors, such as KGF, HGF, and SCF, and that the in vitro photo-induced senescencelike phenotype of fibroblasts leads to the increased production of the same factors (Briganti et al, 2013).…”
Section: Introductionsupporting
confidence: 59%
“…A transcriptional analysis performed in melasma lesions compared to surrounding healthy skin then clearly emphasized the complexity of this disorder by revealing almost 300 genes to be significantly differentially regulated, affecting not only melanocytes but also the dermis component . These results further demonstrate that fibroblast-secreted factors, such as WIF1 (Kim, Lee, & Lee, 2013) or sFRP2 (Kim, Han, Kim, Park, & Kang, 2016), are involved in the pathophysiology of melasma. These data are in line with the reports that fibroblasts isolated from photoaging skin produce a greater amount of promelanogenic growth factors, such as KGF, HGF, and SCF, and that the in vitro photo-induced senescencelike phenotype of fibroblasts leads to the increased production of the same factors (Briganti et al, 2013).…”
Section: Introductionsupporting
confidence: 59%
“…However, positive effects of sFRPs in Wnt signalling have been discovered via stimulation of the β‐catenin pathway . Among skin cells, fibroblasts highly express sFRP2, and the secretion level is significantly upregulated in the hyperpigmentary skin lesions of solar lentigo and melasma and in acutely UV‐irradiated skin . sFRP2 increases melanogenesis in normal human fibroblast–melanocyte cocultures through activation of the β‐catenin–MITF–tyrosinase pathway, showing it to be an effective mesenchymal melanogenic inducer …”
Section: Fibroblastsmentioning
confidence: 99%
“…66 sFRP2 increases melanogenesis in normal human fibroblast-melanocyte cocultures through activation of the b-catenin-MITF-tyrosinase pathway, showing it to be an effective mesenchymal melanogenic inducer. 66 Wnt inhibitory factor (WIF)-1, which is also an important secreted antagonist of Wnt signalling, has been shown to be expressed in human fibroblasts and keratinocytes. A recent study using microarray analysis has indicated that WIF-1 gene expression is significantly reduced in hyperpigmented skin compared with normally pigmented skin in patients with melasma.…”
Section: Scf Edn1mentioning
confidence: 99%
“…Early studies found that sFRP binding to Wnt prevented the activation of Wnt receptors, leading to the initial classification of sFRPs as Wnt signaling inhibitors [27,28]. However, subsequent finding has suggested that sFRP2 functions as a melanogenic stimulator through Wnt/b-catenin signaling, but the precise mechanism needs to be clarified [29]. Kim et al highlighted a certain paracrine role of fibroblast-derived sFRP2 in pigmentation.…”
Section: Sfrpmentioning
confidence: 99%